Presentation of Multiple Myeloma in Ghanaian Patients - Essiaw, L. A. (University of Ghana, 2022)
Multiple myeloma (MM) is an incurable plasma cell dyscrasia, which notably has an age of onset which varies among different races. Several risk factors have been implicated in the disease development and progression including genetics and environmental factors such as pesticide exposure. Despite the population-specific observations in MM presentation, this disease remains largely unexplored in the Ghanaian population. There is very little known about cytogenetic aberrations mediating MM in the African population. The growing prevalence of MM in Ghana necessitates investigating the cytogenetic and environmental risk factors mediating the disease development and presentation. This study therefore, sought to define MM presentations by comparing key clinical metrics at presentation between different racial groups. The study also investigated cytogenetic abnormalities which were present in Ghanaian patients with multiple myeloma. One hundred and six patients had their clinical data at presentation recorded and were age and sex matched with American Caucasian and African American patients. Twenty-two suspected MM patients scheduled for bone marrow aspirate collection were recruited upon receipt of informed consent. Bone marrow aspirates were obtained and demographic details collected using a structured questionnaire. From this study, a significant difference was observed in the M-component, total protein, plasma cell percentage and lactate dehydrogenase levels, with the African cohorts having elevated values. Contrary to earlier reports, females were more affected. Few patients showed indications of kidney damage and there was no observed association between pesticide exposure the disease presentation. Lastly, based on cytogenetic analyses, MYC was the gene found to be predominantly altered in majority of the Ghanaian patients. Also, there were trisomies of odd-numbered chromosomes in 2 out of 5 of the patients.
MPhil. Molecular Biology
Keywords: Multiple myeloma (MM); plasma cell dyscrasia; Ghana